2009
DOI: 10.1016/j.jpeds.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Associated Symptoms in the Ten Days Before Diagnosis of Kawasaki Disease

Abstract: Objective-To describe common associated symptoms within the ten days prior to diagnosis in subjects enrolled in the Pediatric Heart Network's trial of steroid therapy in Kawasaki disease (KD).Study design-Patients with acute KD were enrolled between days 4 and 10 of illness at 8 centers between 2002 and 2004. We defined common associated symptoms as those occurring in ≥ 10% of patients. Principal clinical criteria for KD were not included in this analysis.Results-Among 198 patients, irritability was reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 12 publications
3
83
0
7
Order By: Relevance
“…(5) If the echocardiogram is positive, treatment should be given within 10 days of fever onset or after the tenth day of fever in the presence of clinical and laboratory signs (C-reactive protein [CRP] week of illness and predominantly large weight-bearing joints, especially the knees and ankles, in the second to third week of illness. 102,103 Respiratory findings include peribronchial and interstitial infiltrates on chest radiography; nodular infiltrates occur rarely. Erythema and induration at the site of a previous vaccination with bacille Calmette-Guérin is common in children with KD born in countries where it is used widely.…”
mentioning
confidence: 99%
“…(5) If the echocardiogram is positive, treatment should be given within 10 days of fever onset or after the tenth day of fever in the presence of clinical and laboratory signs (C-reactive protein [CRP] week of illness and predominantly large weight-bearing joints, especially the knees and ankles, in the second to third week of illness. 102,103 Respiratory findings include peribronchial and interstitial infiltrates on chest radiography; nodular infiltrates occur rarely. Erythema and induration at the site of a previous vaccination with bacille Calmette-Guérin is common in children with KD born in countries where it is used widely.…”
mentioning
confidence: 99%
“…3,4 However, there is still much to know about this group of resistant patients, and they warrant further investigation in order to determine factors that contribute to their resistance. Arthritis has previously been reported in Kawasaki disease in 7.5-45% of cases, in both acute or subacute phases, [7][8][9] and although determined to be a transient finding, 1,7 it has also been reported after immunoglobulin therapy. 10,11 It was hypothesized that arthritis would be associated with a higher degree of inflammation and thus immunoglobulin resistance.…”
mentioning
confidence: 99%
“…In addition to diagnostic criteria, KD patients may have many nonspecific clinical features like irritability, vomiting, diarrhea, cough, weakness, abdominal pain, arthralgia and myalgia 1,2,7 . Baker et al 7 found irritability in 50% and weakness in 19% of 198 KD patients and they speculated that these nonspecific symptoms may reflect diffuse vasculitis or be the sequelae of an infectious trigger(s) of KD. Myalgia and fatigue are considered as features that suggest a vasculitic syndrome.…”
Section: Discussionmentioning
confidence: 99%